Transformational Leadership in the Development of MSMEs in Sidenreng Rappang Regency - Zainal, Henni (Universitas Negeri Makassar, 2026)
This study is motivated by the critical role of Micro, Small, and Medium Enterprises (MSMEs) as the backbone of the local economy, particularly in Sidenreng Rappang Regency. Although the number of MSMEs continues to grow, various challenges persist, such as limited innovation, low digital literacy, restricted access to capital, and weak managerial capacity. These conditions indicate that the development of MSMEs requires not only policy support but also leadership capable of driving change, innovation, and collaboration. Transformational leadership is considered relevant because it can inspire, motivate, and guide MSME actors to adapt to economic and technological dynamics. This study employs a qualitative approach using the case study method. The research informants consist of local government officials, MSME facilitators, and MSME operators in Sidenreng Rappang Regency, who were selected through purposive sampling. Data collection techniques included in-depth interviews, observation, and documentation. Data analysis employed an interactive model encompassing data reduction, data presentation, and drawing conclusions, while data validity was tested through triangulation of sources and techniques. The research findings indicate that transformational leadership plays a significant role in SME development through four key dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individual consideration. Visionary and inspirational leadership can increase SME actors’ participation in training programs, encourage product innovation and digital marketing, and strengthen collaborative networks. However, SME development still faces challenges in the form of limited human resources, low digital literacy, and unequal access to financing. Overall, transformational leadership has proven effective in strengthening the capacity and competitiveness of SMEs and contributing to sustainable regional economic growth.